The effect of organizational commitment on the relationship between communication quality and managerial attitudes - Christopher Orpen (Communicare)
The effects of perceived downward and upward communication quality on employee job satisfaction and turnover Intentions was examined among a sample of 101 middle man agers. Hierarchical regression and sub-grouping analyses showed that organizational commitment moder ated both these effects, but that the latter were unaffected by the direc tion of communication, whether it was downward or upward. The re suits confirm the Importance of communication quality in organizations, but make clear that its effects on valued outcomes like job satis faction and intentions to remain In the organization vary, being much stronger among employees attached to the particular organization. Impli cations of the findings for improving communications are developed, and Ideas for further research suggested